2004
DOI: 10.1243/1350650041323403
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastohydrodynamic analysis of elliptical contacts. Part 1: Isothermal and Newtonian lubricant solution

Abstract: Transient elastohydrodynamic lubrication of general elliptical point contacts was analysed in the present study based on multi-level techniques. Both entrainment directions along the major and minor axes of the contact ellipse were considered, together with transient load and speed impulses. In this study, only a Newtonian lubricant and isothermal conditions were assumed. The computing time required for a typical case took only approximately 2 h on a personal computer with a 2.8 GHz central processing unit. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 18 publications
0
41
0
1
Order By: Relevance
“…Thus, using equation (5) to describe the inlet entrainment velocity, equation (1) can now be written as…”
Section: Analytical Solution Improvementmentioning
confidence: 99%
“…Thus, using equation (5) to describe the inlet entrainment velocity, equation (1) can now be written as…”
Section: Analytical Solution Improvementmentioning
confidence: 99%
“…Taking this into account, substituting expressions (6) and (7) into equation (4), and equating coefficients at identical power of y the following expressions can be obtained…”
Section: Problem Statementmentioning
confidence: 99%
“…Mongkolwongrojn, Aiumporsin and Thammakosol (Mongkolwongrojn, et al, 2006) investigated the film temperature and film thickness of liquid-solid lubricants in contact region with non-Newtonian lubricants under sudden overloads and showed the significant effect of solid particles on transient TEHL. Jin, Yang, Cui and Dowson (Jin, et al, 2004 and2005) have analyzed transient EHL of elliptical contacts with Newtonian lubricant to predict the film pressure and film thickness. The results showed that, transient TEHL are similar to EHL.…”
Section: Introductionmentioning
confidence: 99%